Performance Degradation of Subsea Shield Tunnel Segment Accounting for Concrete Strength Loss and Steel Bar Corrosion - Jiaqi Guo; Weiling Yang; Chong Xu; Bo Peng; Jinhai Lin; Yuan Qian (Shock and Vibration)
Subsea shield tunnels usually serve in a typical corrosive marine environment. Under the action of chloride penetration and carbonization, tunnel lining segments are often damaged because of concrete strength loss and steel bar corrosion induced concrete cracking during their service life, which seriously degrades the service performance of the tunnels. A systematical experimental and numerical investigation into the performance degradation of subsea shield tunnel segments accounting for concrete strength loss and steel bar corrosion is presented in this paper. The study demonstrates that chloride penetration decreases the peak strength and elastic modulus of the segment concrete by 42% and 46.1%, respectively. The average of the ratio of dissipated energy to the total energy of dry concrete is much smaller than that of water saturated concrete and chlorine solution saturated concrete, and chloride penetration reduces the energy storage capacity of concrete, and the ability to resist damage is weakened. When steel bars corrode for 120 days, the outer cracks continue to extend, and the concrete around the inner steel bars just begin to crack initiation; when corrode for 20 years, the length of the inner cracks gradually exceeds that of the outer cracks, and the inner cracks initiating from different steel bars coalesce with each other and form a continuous failure surface, causing great serious damage to the segment. Due to the difference in concrete strength, for the outer layer, the evolution processes of steel bar corrosion-induced cracks show the characteristics of early initiation, slow propagation, and late coalescence, and those for the inner layer have the characteristics of late initiation, rapid propagation, and early coalescence. During the whole process the propagation speed of the inner and outer cracks appears to be fast first and then slow. Moreover, the study also illustrates that the final state of segment performance degradation after crack coalescence presents the characteristics of whole lamellar exfoliation of the concrete cover.